Study of serum lactate dehydrogenase level and seasonal variation in preeclampsia and eclampsia with its obstetric outcome - Ciryam, Shilpa S.; E., Gomathy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preeclampsia and eclampsia complicate 6–8% of all pregnancies and lead to various maternal and fetal complications. LDH is an intracellular enzyme and its level is increased in this women due to cellular death. So, serum LDH levels can be used to assess the severity of disease, to improve the maternal and fetal outcome. Studies in several countries have shown higher incidence of the disease in the winter season. This study is being conducted to correlate serum LDH levels and seasonal variation in preeclampsia and eclampsia. Methods: It is a retrospective observational study. Data for 102 cases were collected from the parturition register and patient discharge record from January to December 2016. All singleton pregnant women who came to R L Jalappa Hospital with severe preeclampsia and eclampsia were included in the study. Results: Total of 102 patients were studied. Incidence of the disease was most commonly seen in younger age group, which was statistically significant (p=0.020). Even though most of the cases presented in winter (39), there was no statistically significant association between seasonal variation in occurrence of the disease and serum LDH levels. LDH raised to >800IU/L in the cases was seen more in the younger age group. Conclusions: This study only showed that preeclampsia and eclampsia occurred most commonly in younger women. This study did not show any variation in serum LDH levels in patients presenting in different seasons.